2012
DOI: 10.1111/j.1469-7610.2012.02592.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a computerized working memory training program on working memory, attention, and academics in adolescents with severe LD and comorbid ADHD: a randomized controlled trial

Abstract: Background: Youths with coexisting learning disabilities (LD) and attention deficit hyperactivity disorder (ADHD) are at risk for poor academic and social outcomes. The underlying cognitive deficits, such as poor working memory (WM), are not well targeted by current treatments for either LD or ADHD. Emerging evidence suggests that WM might be improved by intensive and adaptive computerized training, but it remains unclear whether this intervention would be effective for adolescents with severe LD and comorbid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
171
6
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 234 publications
(221 citation statements)
references
References 26 publications
19
171
6
5
Order By: Relevance
“…The lack of far transfer effects suggest that WM training may only be reliable in producing changes in targeted domains and highlights the potential limits of this intervention in producing more widespread improvements. These findings are supported by additional investigations of far transfer effects as a result of WM training which have found no improvements in attention (Green et al, 2012;Thorell et al, 2009), ADHD symptoms (Green et al, 2012), response inhibition (Johnstone et al, 2011), IQ (Holmes et al, 2010) or academic achievement (Gray et al, 2012;Holmes, Gathercole, & Dunning, 2009). However an equal number of studies have found contradictory far transfer effects after WM training, with improvements being present in untrained domains such as attention (Beck et al, 2010;Goldin et al, 2013), ADHD symptoms (Johnstone et al, 2011;Klingberg et al, 2005;Mezzacappa & Buckner, 2010), response inhibition and reasoning (Klingberg et al, 2005;Klingberg et al, 2002).…”
Section: Working Memory Trainingsupporting
confidence: 65%
See 2 more Smart Citations
“…The lack of far transfer effects suggest that WM training may only be reliable in producing changes in targeted domains and highlights the potential limits of this intervention in producing more widespread improvements. These findings are supported by additional investigations of far transfer effects as a result of WM training which have found no improvements in attention (Green et al, 2012;Thorell et al, 2009), ADHD symptoms (Green et al, 2012), response inhibition (Johnstone et al, 2011), IQ (Holmes et al, 2010) or academic achievement (Gray et al, 2012;Holmes, Gathercole, & Dunning, 2009). However an equal number of studies have found contradictory far transfer effects after WM training, with improvements being present in untrained domains such as attention (Beck et al, 2010;Goldin et al, 2013), ADHD symptoms (Johnstone et al, 2011;Klingberg et al, 2005;Mezzacappa & Buckner, 2010), response inhibition and reasoning (Klingberg et al, 2005;Klingberg et al, 2002).…”
Section: Working Memory Trainingsupporting
confidence: 65%
“…For example, improving performance on verbal WM tasks after undergoing training on visuospatial WM tasks. These near transfer effects of WM training have been consistently reported using the CWMT program (Beck, Hanson, Puffenberger, Benninger, & Benninger, 2010;Gray et al, 2012;Green et al, 2012;Klingberg et al, 2005;Klingberg et al, 2002;Mezzacappa & Buckner, 2010;Thorell et al, 2009) as well as alternative working memory training programs; Jungle Memory (Alloway et al, 2013) and Mate Marote (Goldin et al, 2013).…”
Section: Working Memory Trainingmentioning
confidence: 92%
See 1 more Smart Citation
“…Reason for exclusion Barnett et al [86] Participants are teachers Benyakorn et al [87] Not interventional Bishop [88] Intervention not technology Bonarini et al [89] Population focus not ADHD Bul et al [90] Outcome measures do not assess ADHD-related difficulties Chan et al [91] Not interventional Chen et al [92] Not interventional Christiansen et al [93] Intervention reliant on others Dale and Grut [94] Not exclusively for ADHD Duffy [95] Population focus not ADHD Enebrink et al [96] Population focus not ADHD References Reason for exclusion Epstein et al [97] Intervention reliant on health care professionals Fiellin et al [98] Population focus not ADHD Frutos-Pascual et al [99] Population focus not ADHD Frutos-Pascual and GarciaZapirain [100] Participants typically developing, not ADHD Gray et al [72] ADHD not primary diagnosis of participants Halperin et al [101] Intervention not technology Janeslätt et al [102] Intervention not technology Kim et al [103] Intervention not technology Lim et al [104] Intervention reliant on health care professionals Mazurek and Engelhardt [105] Not interventional Myers et al [106] Participants ADHD diagnosis not confirmed Nie et al [107] Intervention not technology Pandria et al [108] Not interventional Rohani et al [109] Participants ADHD diagnosis not confirmed Rosch and Mostofsky [110] Not interventional Schafer et al [111] Participants not received ADHD diagnosis Schuck et al [112] Participants not received ADHD diagnosis Shah et al 2012 Not interventional Silva et al [113] Technology as outcome measure, not intervention Steeger et al 2016 Participants ADHD diagnosis not confirmed Stephenson [114] Population focus not ADHD Tse et al …”
Section: Appendix 2: References and Reasons For Exclusionmentioning
confidence: 99%
“…Given the growing research base on the associations among working memory and intelligence (Cornoldi & Giofre, 2014), and working memory and learning (Alloway & Copello, 2013), it is easy to see why a majority of the cognitive training programs target working memory. Certainly, most of the studies do cite improvements in working memory (Beck, Hanson, & Puffenberger, 2010; Dunning et al, 2013; Gray et al, 2012; Holmes & Gathercole, 2014; Wiest, Wong, Minero, & Pumaccahua, 2014), but pretest to post‐test gains have also been documented in fluid reasoning (Barkl, Porter, & Ginns, 2012; Jaeggi et al, 2008; Mackey, Hill, Stone, & Bunge, 2011), processing speed (Mackey et al, 2011), reading (Loosli, Buschkuehl, Perrig, & Jaeggi, 2012; Shalev, Tsal, & Mevorach, 2007), computational accuracy (Witt, 2011), and attention (Rabiner, Murray, Skinner, & Malone, 2010; Tamm, Epstein, Peugh, Nakonezny, & Hughes, 2013). …”
mentioning
confidence: 99%